The importance of natural fractures in a tight reservoir for potential CO 2 storage:A case study of the upper Triassic-middle Jurassic Kapp Toscana Group (Spitsbergen, Arctic Norway) - Ogata, K.; Senger, K.; Braathen, A.; Tveranger, J.; Olaussen, S. (Geological Society, London, Special Publications, 2014)
In the Longyearbyen CO 2 laboratory project, it is planned to inject carbon dioxide into a Triassic-Jurassic fractured sandstone-shale succession (Kapp Toscana Group) at a depth of 700- 1000 m below the local settlement. The targeted storage sandstones offer moderate secondary porosity and low permeability (unconventional reservoir), whereas water injection tests evidence good lateral fluid flow facilitated by extensive fracturing. Therefore, a detailed investigation of fracture sets/discontinuities and their characteristics have been undertaken, concentrating on the upper reservoir interval (670-706 m). Datasets include drill cores and well logs, and observations of outcrops, that mainly show fracturing but also some disaggregation deformation bands in the sandstones. The fracture distribution has a lithostratigraphical relationship, and can be subdivided into: (A) massive to laminated shaly intervals, offering abundant lower-angle shear fractures; (B) massive to thin-bedded, heterogeneous, mixed silty-shaly intervals, with a predominance of non-systematic, pervasive bed-confined fractures; and (C) massive to laminated, medium- to thick-bedded, fine- to coarse-grained sandstones with a lower frequency of mostly steep fractures. These domains represent pseudo-geomechanical units characterized by specific fracture sets and fracture intensity, with indicated relationships between the bed thickness and fracture intensity, and with domains separated along bedding interfaces. We discuss the impact of these lithostructural domains on the fluid flow pathways in the heterolithic storage unit.